ETHICAL DYNAMICS IN THE IMPLEMENTATION OF REWARDS AND PUNISHMENT IN ISLAMIC EDUCATION - Andi Abd. Muis; Nur Amalina Abdul Rahman; Mardiah Wahyuni; Siti Rondhiyah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
Reward and punishment are pedagogical strategies commonly employed in Islamic education to shape students’ behavior and moral character. However, practices that are not grounded in ethical principles may lead to dependence on external motivation and have negative effects on students’ psychological development. This study aims to analyze the ethical dimensions of the implementation of reward and punishment from the perspective of Islamic education as well as contemporary critiques in studies of learning motivation. This research adopts a qualitative approach through a literature review, with data sources derived from the Qur’an, Hadith, books, and relevant scholarly journals. The data were analyzed using a descriptive-analytical method, focusing on Islamic ethical values such as justice (‘adl), compassion (rahmah), wisdom (hikmah), and the educational orientation of tarbiyah. The findings indicate that reward is effective in enhancing positive motivation when applied proportionally and meaningfully, whereas punishment is justified only as an educational tool that aims to educate without undermining students’ dignity. Contemporary psychological critiques emphasize that an imbalance in the application of reward and punishment may weaken intrinsic motivation. The implications of this study underscore the importance of ethical and reflective instructional strategies that position reward and punishment as supporting instruments for character education. Ethical practices grounded in Islamic values contribute to the development of students’ intrinsic motivation and moral responsibility in accordance with the objectives of Islamic education.